Aerodynamic drag characteristics of skaters in speed skating team pursuit formation - Zhang, Y.; Li, B. (European Journal of Mechanics - B/Fluids, 2024)
This study focused on the effects of longitudinal and lateral spacing on the aerodynamic drag characteristics of the whole team and each member in speed skating team pursuit competition (SSTPC). To further understand the effect of formation spacing on the aerodynamic drag distribution on the skater body surface, a combination of experiments and numerical simulations was performed. Three identical mannequins were used to conduct wind tunnel tests and the results were compared with computational fluid dynamics (CFD) simulation results obtained using a 3D digital model of the mannequin. The results showed that, as the longitudinal spacing decreased, greater drag reduction was gained by the whole team and three members (leading, middle, and last). When the longitudinal spacing was 1.05 L (L refers to body length), the whole team and the three members had drag reduction of 31.5%, 10.1%, 42.1%, and 42.3%, respectively. After each 0.1 L increase in longitudinal spacing, the whole team and the leading, middle, and last skaters lost 2.0%, 1.8%, 2.3%, and 1.8% of their drag reduction, respectively. When the leading skater moved laterally to 0.2 W (W refers to body width), the whole team and the last skater achieved an additional drag reduction of 0.7% and 4.2%, respectively. The CFD simulation results further revealed that the body surface drag distribution trend of the leading skater was similar to that of the isolated skater, with the largest proportion of drag being located on the calves. The drag on the torsos, thighs and calves of the middle and last skaters was significantly smaller than that on the corresponding parts of the isolated skater, and its proportion was comparable.